Managing differentiated services in upstream EPON - Mohamed Radzi N.A.; Din N.M.; Al-Mansoori M.H.; Abdul Majid Mohd.S. (2023)
In order to enhance the bandwidth utilization while maintaining the required quality of service (QoS), an efficient dynamic bandwidth allocation (DBA) algorithm that supports global priority has been proposed in upstream Ethernet passive optical network (EPON). The algorithm aims to allocate bandwidth to different traffic classes according to the priority as a whole. The simulation is done using MATLAB by comparing the proposed algorithm with a DBA algorithm found in the literature. The proposed algorithm shows an improvement as high as 11.78% in terms of bandwidth utilization and reduces expedited forwarding (EF), assured forwarding (AF) and best effort (BE) delay as high as 25.22%, 18.96% and 21.34% respectively compared to Min's DBA. 2011 Springer-Verlag.